Dilatated Cardiomyopathy In Two Month Old Puppy - Haris Muhamad Ikhsan; Putu Ayu Sisyawati Putriningsih (Universitas Airlangga, 2021)
Background: Canine dilated cardiomyopathy (DCM) is a disease that results in a decreased ability of the cardiac contraction to generate pressure to pump blood through the vascular system. DCM is characterized by dilation of the ventricles with ventricular wall thinning. Purpose: The DCM case in Indonesia is rarely reported; therefore, this paper contains information about dilatated cardiomyopathy in a 2-month-old puppy. Case Analyze: A two-month-old local dog arrived with a complaint about coughing, loss of appetite, fatigue, and swelling on extremities, also having a history of seizures and bloody diarrhea. Physical examination shows that the patient breathes using abdominal type and polypnea, tachycardia pulse, pale mucose, and dehydration. Electrocardiogram result shows tachycardia sinus and abnormality in the depression of ST-segment. Radiography examination shows heart dilation and liquid accumulation in the thoracic cavity and abdomen. Hematology routine examination shows microcytic hyperchromic anemia, leucocytosis, and eosinophilia. Feces examination resulted in negative. Pathology anatomy examination show dilatated cardio, pulmonum hepatization, fluid accumulation in the thoracic cavity and abdomen cavity. Result: According to anamnesis, clinical examination, laboratory examination, and anatomy pathology examination can be concluded that the dog, in this case, is diagnosed with dilatated cardiomyopathy.